The impact of evidence from clinical trials on counselling for over‐the‐counter drugs: A national survey of pharmaceutical staff in German pharmacies. (3rd September 2019) - Moritz, Katharina; Seiberth, Jasmin Mina; Schiek, Susanne; Bertsche, Thilo
Abstract: What is known and objective: Evidence from clinical trials should form the foundation of healthcare advice. Comparatively little has been investigated about the implementation of evidence in over‐the‐counter (OTC) counselling in community pharmacies. The objective of this study was to explore the current impact of clinical trials on OTC counselling from the perspective of pharmaceutical staff. Methods: Pharmaceutical staff in German community pharmacies were invited to participate in a nationwide cross‐sectional survey using SoSci Survey. Within the questionnaire, the following items were queried: (i) attitudes towards influencing factors on OTC drug recommendation, (ii) practical procedure of OTC drug recommendations, (iii) experiences and challenges in handling clinical trials, and (iv) current and desired continuing education on self‐medication. Multiple logistic regression was employed to identify predictors for OTC recommendations based on clinical trials in routine. Results and discussion: In total, 1068 participants completed the survey. (i) Clinical trial data were rated as 'very important' for drug recommendations by 33% and as 'rather important' by 50%. (ii) 8% reported that they base their recommendations on clinical trial data 'in almost all consultations', 40% 'in most consultations'. (iii) 69% faced difficulties in including clinical trial data into their counselling. (iv) 7% read original clinical trials at least once a month. Predictors for routine OTC recommendations based on clinical trials were as follows: male gender, university degree, clinical trials considered to be important for recommendations, inclusion of clinical trials in counselling assessed as easy, higher frequency of reading specialized literature per year, increasing number of working pharmacists in the pharmacy, and more casual than regular customers in the pharmacy. What is new and conclusion: Most of the pharmaceutical staff recognize the importance of clinical studies for self‐medication advice. Based on self‐report, however, clinical trial data are not taken routinely into account in practice. Only a minor proportion of staff routinely deal with studies. Therefore, appropriate instruments are required to make knowledge from clinical trials available in community pharmacies. Abstract : We performed a nationwide cross‐sectional survey among pharmaceutical staff. The aim was to investigate the impact of findings from clinical trials on self‐medication counselling. Our study revealed a distinct gap between a positive attitude towards evidence‐based decision‐making for self‐medication advice and its actual implementation in daily practice. In fact, the pharmaceutical staff rarely dealt with original trial data. Furthermore, they reported various problems in the search and appraisal of clinical trial data.